2016
DOI: 10.14393/bj-v32n4a2016-32963
|View full text |Cite
|
Sign up to set email alerts
|

Perception of laypersons and dentists regarding esthetic facial changes: a systematic review

Abstract: The need for greater understanding of subjective standards of beauty is important when combining a successful dental plan with the real needs of patients. This study aimed to perform a systematic review to assess whether dentists are more critical in assessing facial esthetics than laypersons. The cross-sectional studies selected compared dentists and laypersons regarding the perception of facial changes through photographs. The survey was conducted in four databases (PubMed, SciELO, LILACS, and OpenGrey) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The observed results pointed that the health professional's valuation is in between Lawyers perceptions and Laypeople perception. Considered of fundamental importance to the forensic health professional perception, as pointed by the literature, tend to be more critical in relation to facial aesthetics [11] [12] [13] [14]. Yet this region is highly visible and often exposed for social communication justifying the need for major attention to aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…The observed results pointed that the health professional's valuation is in between Lawyers perceptions and Laypeople perception. Considered of fundamental importance to the forensic health professional perception, as pointed by the literature, tend to be more critical in relation to facial aesthetics [11] [12] [13] [14]. Yet this region is highly visible and often exposed for social communication justifying the need for major attention to aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not the case in our study where there were remarkable variations among different dental professionals although they perceived these components more precisely when compared to LP. In a recent systematic review, Barbosa et al 11 conducted their review in four databases; aimed to assess whether dentists are more critical in assessing facial esthetics than laypersons. Three relevant articles [12][13][14] were selected from an initial total of 979 articles collected.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested "Further studies with more standardized methods are suggested in order to definitely clarify who is more critical in the subjective assessment of facial characteristics". 11 To the best of our knowledge, this is the first study that assessed all facial esthetic components once and among a large sample of individuals who had different dental education and clinical experience. The maximum number of raters in their study was 30, 14 while the minimum number of raters in this study is 74 (Dental Specialists).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time spent to understand the patients' true interests should be valued, and it is extremely important to explain the objectives, possibilities and limitations of orthodontic treatment [11]. The best way to gain trust and obtain patient cooperation is by giving importance to interpersonal relationships and, consequently, investing in the professional-patient relationship [12][13][14].…”
Section: Introductionmentioning
confidence: 99%